PEMANFAATAN AMPAS TAHU DALAM PENGOMPOSAN LIMBAH JAMUR - Daniati, Daniati (Bioscientist : Jurnal Ilmiah Biologi, 2013)
The problem of waste disposal that does not follow the rules almost always have a negative impact on the environment both in terms of aesthetics, environmental health and quality of human life. Organic waste derived from household activities is actually harmless, making it easier to handle than liquid and solid wastes containing hazardous materials from factories. Handling household waste is cheap and easy is composting it into compost. One alternative that can be done is to use the waste and waste to make compost with the addition of organic materials such as EM-4 and tofu dregs. In this research will try to utilize the tofu waste as activator in the composting process as a substitute of EM-4. Where the type of tofu dregs used is derived from byproducts in the preparation of tofu in solid form and obtained from the soybean expanse slurry, which is commonly found in tofu entrepreneurs, dregs of tofu mixed with (waste mushroom, oyster mushroom waste, bran, sugar, lime betel and water to taste). This study aims to determine the utilization of tofu pulp in composting of mushroom waste. This research was conducted in Perum Jalan Panji Asmara Number 1 District of Sekarbela, West Lombok regency, from February to March 2013. This research is experiment with qualitative research approach using Randomized Complete Design (RAL) with experiment consist of two treatment factors, that is EM4 and tofu, each treatment factor repeated 3 repetitions. Observational data were analyzed using descriptive analysis. Parameters observed were temperature, odor, color, and humidity. From the results of the study concluded that the use of tofu waste activator in composting of mushroom waste faster than the use of EM4 activator because the dregs know it contains lots of ammonia and quickly decompose, thus accelerating in the composting process.